2023
DOI: 10.1002/aenm.202300301
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Acceptor Enables High‐Performance and Robust All‐Polymer Solar Cells with 17.4% Efficiency

Abstract: (2 of 10)that of SMAs limits the short-circult current densities (J SC s), and the unfavorable morphology caused by large conjugated lengths ang high molecular weights of P A and P D materials tends to suppress the fill factors (FFs). [38][39][40][41][42] To solve these issues, "polymerized small molecule acceptor" (PSMA) strategy, [43,44] ternary strategy, [45] and device engineering [30,31,33,46] are considered as efficient approaches to be developed continually. Among various device optimization methods, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Moreover, the PM6: NFA9 blend exhibits decent thermal stability in devices (Figure C), suggesting excellent morphological stability. They further revealed that the dimer ( NFA14 ) of Qx-based acceptors is much more stable than the relevant polymer (poly-NFA14) in PM6-based OSCs under photoaging (Figure D) . Our group unraveled how the local isomerization of substitutions on cross-conjugated side groups influences the geometry and noncovalent interactions of molecules, thereby having great impact on the device stability .…”
Section: Structure–property Relationshipmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, the PM6: NFA9 blend exhibits decent thermal stability in devices (Figure C), suggesting excellent morphological stability. They further revealed that the dimer ( NFA14 ) of Qx-based acceptors is much more stable than the relevant polymer (poly-NFA14) in PM6-based OSCs under photoaging (Figure D) . Our group unraveled how the local isomerization of substitutions on cross-conjugated side groups influences the geometry and noncovalent interactions of molecules, thereby having great impact on the device stability .…”
Section: Structure–property Relationshipmentioning
confidence: 85%
“…Chen et al further developed a series of dimer-like acceptors based on biaxially conjugated CH-series molecules. They used a “terminal coupling” strategy to synthesize a horizontally linked dimer NFA14 , achieving a decent PCE of 16.62% when coupled with PM6 . Besides, they employed a “core fusing” strategy to obtain a vertically coupled dimer NFA15 that has a symmetrical and coplanar conjugated skeleton .…”
Section: Biaxially Conjugated Non-fullerene Acceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the long-term stability of OSCs is expected to get a striking improvement due to greatly suppressed molecular diffusion in blended films . Note that the most conventional way to build dimer acceptors is “terminal coupling” through end units (brominated 2-(3-oxo-2,3-dihydro-1 H -inden-1-ylidene)­malononitrile groups) of small molecular acceptors at present, just like plenty of dimer acceptors based on Y-series molecular backbones or CH-D1 in Figure . However, this strategy to construct dimer acceptors will bring about several unavoidable shortcomings: (1) Inferior intermolecular packings, especially for the “E/E” mode .…”
Section: D Conjugation Extended A–d–a Type Ch-series Acceptorsmentioning
confidence: 99%
“…Mechanical robustness is one of the most attractive properties of all-polymer blend films. Most polymer acceptors consist of large fused rings and fully conjugated backbones to ensure efficient charge transport and strong light absorption. However, the backbone in fully conjugated polymers is typically very rigid which favors strong, structurally regular aggregation which often leads to brittle polymer acceptors and BHJ blend films . Few all-PSC studies have introduced nonconjugated units into the polymer backbone to understand their effect on the optical, electronic, and mechanical properties, and fewer studies have systematically addressed the effect of polymer acceptor conjugation length on the mechanical robustness of the corresponding films and blends .…”
mentioning
confidence: 99%